Legal status of national minorities in Ukraine: security problems and realities - Tsymbalistyi, Taras; Khamyha, Vitaliia (Actual problems of law (Aktual’ni problemi pravoznavstva), 2020)
The article is devoted to the study of the legal status of national minorities in Ukraine, its problems, the definition of the main guidelines in the study of the contradictory issue of ensuring the rights of national minorities through the analysis of fundamental legal acts and the real situation in the country, formulation of conclusions and certain principles that will improve the situation of minorities. in Ukraine. As of today, the concept of the legal status of national minorities in Ukraine is not sufficiently researched and there is no perfect legislative framework aimed at improving their status. For Ukraine, as for any multiethnic state, the issue of national minorities is perpetually relevant and needs constant study and analysis. The formation of Ukraine as an independent state has put on the agenda both a theoretical and a practical task - to develop its own concept of national policy.